2016
DOI: 10.1037/cns0000108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring affect integration in children with anxiety disorders: A pilot study.

Abstract: Affect integration is considered central to mental health. We define affect integration in terms of the affect consciousness construct as degrees of awareness, tolerance, nonverbal, and conceptual expression of 11 affects (Monsen, Eilertsen, Melgård, & Odegård, 1996). We assessed the construct using a child-adapted version of the semistructured Affect Consciousness Interview and separate scoring scales (Taarvig, Solbakken, Grova, & Monsen, 2015). We administered this interview to 8 children who met the criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
(121 reference statements)
4
6
0
Order By: Relevance
“…The results indicate that the ACI provides information that is highly consistent on an overall, dimensional level, with more nuanced information on the level of individual affect. The results were consistent with the hypotheses and corresponds to earlier findings indicating that the Affect Consciousness score and the four dimensions gives the best overall view of affect integration, while a consideration of integration of individual affects can give clinically useful information on an individual level ( 2 , 19 , 25 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results indicate that the ACI provides information that is highly consistent on an overall, dimensional level, with more nuanced information on the level of individual affect. The results were consistent with the hypotheses and corresponds to earlier findings indicating that the Affect Consciousness score and the four dimensions gives the best overall view of affect integration, while a consideration of integration of individual affects can give clinically useful information on an individual level ( 2 , 19 , 25 ).…”
Section: Discussionsupporting
confidence: 91%
“…Using the affect consciousness interview (ACI) for children, Taarvig et al ( 3 ) found that higher affect integration was linked to better social competency and fewer psychopathology symptoms in 11-year old children with internalizing difficulties. Another study exploring a subset of the same data ( 19 ) found lower integration of particularly fear, shame, guilt, and anger in anxious children.…”
Section: Affect Integration and Psychopathology In Childrenmentioning
confidence: 95%
See 3 more Smart Citations